Gross anatomy learning using radiological images (galeri) : its impact on first-year medical students' comprehension, engagement, and cognitive load - Sa'hari @ Ramli, Nur Atiqah (2021)
Background: A sound anatomy knowledge is the foundation to safe clinical practice. However, due to limited contact hours and the nature of anatomy knowledge that is packed with information, medical students tend to learn anatomy using surface-level approach. As a result, the information is not stored in the long-term memory, which would cause difficulty in retrieving the information in future practice. Furthermore, the Coronavirus disease 2019 (COVID-19) pandemic has resulted in the lack of kinaesthetic experience in anatomy learning, and thus making it less engaging. Learning anatomy in clinical context has been perceived by students to be more engaging and effective. In this imaging era, radiology has been commonly used as a context in learning anatomy. In view of its potential to improve anatomy learning, the impact of the use of radiological images as clinical context needs to be explored further. Objective: To determine the impact of Gross Anatomy Learning Using Radiological Images (GALERI) e-learning on first-year students’ gross anatomy learning in Universiti Sains Malaysia. Method: Two types of supplementary e-learning courses on a selected anatomy topic were developed based on ELED framework: (i) Gross Anatomy Learning Using Radiological Images (GALERI), and (ii) control e-learning using non-radiological images. Their impact on gross anatomy learning was studied in a randomised controlled trial conducted on 82 consented first-year medical students. By applying the stratified randomisation method, the participants were divided into two groups, namely GALERI group and control group. The GALERI group was assigned to complete GALERI e-learning, whilst the control group was assigned to attend to the control e-learning. On Day-1 of intervention, participants in both groups were given a pre-e-learning assessment to measure their baseline knowledge. On the next day, they were given the access to the assigned e-learning course according to their respective group. Immediately after completing the e-learning course, all participants were required to fill in two questionnaires to measure their engagement level and cognitive load. Then, the participants were given post-e-learning assessment to evaluate their knowledge acquisition after completing the course. The improvement in their knowledge acquisition was calculated from the difference in the pre- and post-e-learning assessments. In addition, the participants were invited give an open feedback on the experience of using the e-learning courses in their anatomy learning. Independent t-test was conducted to analyse the difference of pre- and post-e-learning assessment scores, engagement score and cognitive load score between the two groups. Paired t-test was used to analyse the change in pre- and post-e-learning scores within each group. Repeated measure ANOVA was performed to analyse the improvement in knowledge acquisition and thematic analysis was conducted to interpret the open feedback data. Results: The analysis showed that there was no significant difference in the pre- and post-e-learning scores between the two groups. Both groups showed significant improvement in their comprehension of the selected anatomy topic after completing the e-learning courses. The students’ engagement and cognitive load level were also not significantly different between the two groups. Nevertheless, GALERI e-learning has managed to have positive impact on students’ perceived value of learning, cognitive engagement, and emotional engagement. Conclusion: The significant improvement in assessment scores highlights that students benefited greatly from e-learning course that supplement their learning beyond contact hours. However, the use of radiological images as clinical context was not proven to have an advantage on students’ comprehension, engagement and cognitive load. Nevertheless, the potential of radiological images in anatomy learning can be explored further by overcoming the limitations in this study.